2022
DOI: 10.3389/fped.2022.852034
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Extracellular Vesicles for the Treatment of Bronchopulmonary Dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is the most common chronic respiratory disease in premature infants. However, there is a lack of effective treatment. Mesenchymal stromal cells derived extracellular vesicles (MSC-EVs), as nano- and micron-sized heterogeneous vesicles secreted by MSCs, are the main medium for information exchange between MSCs and injured tissue and organ, playing an important role in repairing tissue and organ injury. EVs include exosomes, microvesicles and so on. They are rich with various pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The exosomes secreted by these umbilical cord blood MSCs can regulate related diseases through miRNA, regulate proliferation and migration-related TGF-β signaling pathways 35 , and also regulate inflammation-related GSK3β/Wnt/β 36 and IL-6/STAT3 pathway 37 . Umbilical cord blood exosomes are primarily protective in lung disease 38 . Another study of ours also showed that exosomes derived from healthy term umbilical cord blood can alleviate hyperoxia-induced lung injury 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The exosomes secreted by these umbilical cord blood MSCs can regulate related diseases through miRNA, regulate proliferation and migration-related TGF-β signaling pathways 35 , and also regulate inflammation-related GSK3β/Wnt/β 36 and IL-6/STAT3 pathway 37 . Umbilical cord blood exosomes are primarily protective in lung disease 38 . Another study of ours also showed that exosomes derived from healthy term umbilical cord blood can alleviate hyperoxia-induced lung injury 39 .…”
Section: Discussionmentioning
confidence: 99%
“…23 components of the proteome secreted by cells and play a crucial role in mediating intercellular communication. 24 Due to their smaller size, 25 favorable biostability, low immunogenicity, biocompatibility and potential of large-scale production, 22 our research focus on the impact of BMSC-Exos on ECs. In this study, they were extracted and purified for characterization, and further investigated for the potential mechanisms by which they exert their biological effects.…”
Section: Microscopic Staining Analysismentioning
confidence: 99%
“…It dramatically influences the composition of their secretome, allowing for the production of disease-specific exosomes [ 209 ]. Accordingly, they may display anti-inflammatory [ 210 ], pro-angiogenic [ 211 ], anti-apoptotic, or anti-oxidative properties [ 212 ]. Cell-free therapies offer many advantages over cell-based therapies: a higher scale of production, a lesser risk of contamination with CMV and HSV, the possibility for long-term storage and easier transportation, and fewer ethical considerations [ 213 ].…”
Section: Exosomes As Therapeutic Toolsmentioning
confidence: 99%